Field notes contributed by Robert K. Myers, spring 1984 - Myers, Robert K.et al (1984)
Field notes contributed by Robert K. Myers, spring 1984, with some observations shared with Francis L. Moore. There were 22 species identified. In a cover letter to Thomas H. Kent, dated May 31, 1984, Myers said it was the poorest spring migration since he started keeping records in 1978. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed